Voice-Activated In-Car Assistant With Natural Language Processing (International Journal of Scientific Research in Science and Technology, 2025)
"Voice-Activated In-Car Assistant with Natural Language Processing" paper combines natural language processing and voice recognition to provide a clever, hands-free car control system. The system, which uses a Raspberry Pi as its primary microprocessor, uses a USB microphone to pick up voice instructions, giving the user control over a number of in- car features. To ensure safety when navigating, an ultrasonic sensor (HC-SR04) is employed to identify impediments. A DHT11 sensor provides environmental feedback by measuring temperature and humidity in real time, while a servo motor controls the car’s windows. The direction of the vehicle is controlled by a motor driver, while audio output is provided by a speaker for notifications, song playback, and voice responses. Email warnings for particular conditions, including barrier detection or extremely high or low temperatures, are also included in the system. By enabling users to control the robot’s movement, check the weather, open the windows get safety alerts, and play music—all with simple voice commands—this smart assistant improves in-car convenience.